2021
DOI: 10.3390/sym13081379
|View full text |Cite
|
Sign up to set email alerts
|

Study on Low-Frequency Band Gap Characteristics of a New Helmholtz Type Phononic Crystal

Abstract: In order to solve the problem of low-frequency noise of aircraft cabins, this paper presents a new Helmholtz type phononic crystal with a two-dimensional symmetric structure. Under the condition of the lattice constant of 62 mm, the lower limit of the first band gap is about 12 Hz, and the width is more than 10 Hz, thus the symmetric structure has distinct sound insulation ability in the low-frequency range. Firstly, the cause of the low-frequency band gap is analyzed by using the sound pressure field, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Conventional theoretical designs often struggle to achieve the requirements of low added mass, vibration isolation, and low sound isolation frequencies. Later, it was found that the periodic structure has bandgap properties [5][6][7][8], and elastic waves are blocked in the bandgap range. Consequently, new composites with periodic structures, such as PC [9,10], have received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional theoretical designs often struggle to achieve the requirements of low added mass, vibration isolation, and low sound isolation frequencies. Later, it was found that the periodic structure has bandgap properties [5][6][7][8], and elastic waves are blocked in the bandgap range. Consequently, new composites with periodic structures, such as PC [9,10], have received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Phonon crystals can be used to control the propagation of elastic waves, and thereafter, acoustic metamaterials developed on this basis have potential applications in the fields of national defense as well as vibration and noise reduction in national economy and daily life, [1] Yuan X [2] designed a two-dimensional phonon crystal using three materials and achieved a sound insulation of 47.3 dB by adjusting the parameters. Qi Yang [3] designed a conical phonon crystal plate that produced a large broadband at 44.4-707.2 Hz by tuning the geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Quinteros et al [9] devised a methodology for optimizing the topology of sandwich panels by employing cellular truss cores, thereby enhancing vibration absorption in honeycomb structures commonly used in extensive transportation vehicles such as aircraft. Furthermore, practical applications have been explored in compartments [10] and UAV formation control [11]. As research progresses, the pursuit of broad-frequency characteristics has yielded remarkable metamaterials.…”
Section: Introductionmentioning
confidence: 99%